(untitled) (Gaceta Técnica, 2019)
The research work presented was carried out with the purpose of evaluating GISWater and HECgeoRAS Geographic Information System (GIS) related tools, which function as a connection node between the HEC-RAS model and the QGIS and ArcGIS software respectively. . Here the conditions of creation of the digital model of the land are leveled, with the purpose of obtaining a final result from a parity of circumstances. The case study chosen to obtain the results was the Quebrada Borure located in the city of Barquisimeto, State of Lara, Venezuela. Once both solutions provided by the HEC-RAS hydraulic modeler were obtained, the correlation between both products was determined, being high, close to the value of the unit, reason why it could be concluded that both tools are applicable in the data processing for the HEC-RAS model, with the advantage that GISWater is a free license and works under the geographic information system QGIS with the same characteristics